Test MFT Hockey Women Athletes in Central Java Facing PON XIX West Java Year 2016 - Darmanto, Fery (Universitas Negeri Semarang, 2017)
The aim of the research was to know the physical condition of female Hockey athletes of Central Java especially in cardio capacity endurance to participate in PON XIX West Java, 2016. The type of this research was quantitative descriptive, with 22 female athtletes as the population. The technique in data collection used was population research that is all samples in this study were taken all. The sampling method used was quantitative technique with descriptive approach. The result of this research was the average physical condition especially in endurance was tested using the MFT in the degrees of being. It was proven that the average VO2max of female Hockey athletes of Central Java was 39.6 ml/kg/min or 8.5 in MSFT reverse. The conclusion was the physical condition of the female Hockey athletes of Central Java who would attend PON XIX 2016 in West Java was in moderate level.